The synthesis of peptide‐conjugated poly(2‐ethyl‐2‐oxazoline)‐b‐poly(L‐lactide) (PEtOx‐b‐PLA) polymeric systems through the combination of controlled polymerization techniques and click reactions. Issue 17 (16th November 2020) - Ozkose, Umut Ugur; Gulyuz, Sevgi; Parlak Khalily, Melek; Ozcubukcu, Salih; Bozkir, Asuman; Tasdelen, Mehmet Atilla; Alpturk, Onur; Yilmaz, Ozgur
Abstract: To optimize the therapeutic effect of pharmaceutical agents, drug delivery systems tailored from FDA‐approved polymers like poly(L‐lactide) (PLA) is an effective strategy. Because of their hydrophobic character, these systems greatly suffer from reduced circulation time thus, amphiphilic block copolymers became favorable to overcome this limitation. Of them, poly(oxazoline)‐ b ‐poly(L‐lactide) are of choice as poly(oxazoline) (PEtOx) is compatible, biodegradable, while exhibiting minimum cytotoxicity. To tailor selective drug targeting drug delivery systems, whereby their selectivity for tumor tissues is maximized, these polymers should be decorated with so‐called tumor‐homing agents, such as antibodies, peptides and so forth. To this respect, we designed a new block copolymer, allyl‐poly(2‐ethyl‐2‐oxazoline)‐ b ‐poly(L‐lactide) allyl‐(PEtOx‐ b ‐PLA) and its subsequent conjugation to tumor‐homing peptides, peptide‐18, and peptide‐563 at the terminal position. In this manuscript, we report our synthetic route to obtain this building block and its conjugation to tumor‐homing agents. Abstract :